2012
DOI: 10.1136/bcr-02-2012-5916
|View full text |Cite
|
Sign up to set email alerts
|

Giant mesenteric cyst: a rare cause of abdominal distension diagnosed with CT and managed with ultrasound-guided drainage

Abstract: SummaryThis rare cystic lesion has an approximate incidence of 1 in 200 000. This patient complained of abdominal distension and was diagnosed with a giant mesenteric cyst measuring 26 cm in height using CT imaging. She underwent a successful ultrasound-guided drainage, which is not previously reported in the literature. This represents utilisation of an established procedure in a novel situation. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…They are generally regarded as benign lesions and the typical recommendation for treatment is complete resection in order to minimize recurrence. There have been reports of laparoscopic excision, even of giant cysts, which often require intraoperative aspiration to assist in removal 10,11 . The incidence of malignancy within mesenteric cysts is often cited to be up to 3%, which originates from Kurtz's analysis of 162 cases reported in the English literature between 1950 and 1986 4 .…”
Section: Discussionmentioning
confidence: 99%
“…They are generally regarded as benign lesions and the typical recommendation for treatment is complete resection in order to minimize recurrence. There have been reports of laparoscopic excision, even of giant cysts, which often require intraoperative aspiration to assist in removal 10,11 . The incidence of malignancy within mesenteric cysts is often cited to be up to 3%, which originates from Kurtz's analysis of 162 cases reported in the English literature between 1950 and 1986 4 .…”
Section: Discussionmentioning
confidence: 99%
“…1). Namnażające się adipocyty są objęte torebką, a w obrazie USG zmiana jest jednorodna i zwykle ma lekko podwyższoną echogeniczność oraz gładkie zarysy; niekiedy poszczególne zrazy są oddzielane przez cienkie przegrody włókniste, a w kolorowym dopplerze zmiana nie jest unaczyniona (1)(2)(3)(4) . Zdarza się, że nowotwór występuje w formie mnogiej (5) (ryc.…”
Section: Pierwotne Nowotwory łAgodne Zawierające Adipocyty Położone W Tłuszczu Wewnątrzbrzusznymunclassified
“…Sometimes, individual lobules are separated from one another by thin fibrous septa. Color Doppler shows no signs of flow (1)(2)(3)(4) . At times, this tumor can be encountered in a multiple form (5) (Fig.…”
Section: Pierwotne Nowotwory łAgodne Zawierające Adipocyty Położone W Tłuszczu Wewnątrzbrzusznymmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenteric cysts are rare tumours, with an incidence of 1/100,000 -1/250,000 [1] and large mesenteric cysts are even less common [2]. The biggest review of case reports found these cysts in the range of 2-36 cm, with 60% associated with the small bowel mesentery, 24% with large bowel and 16% in the retroperitoneum.…”
Section: Introductionmentioning
confidence: 99%